Papel dos Colegiados no desenvolvimento de uma política de integração territorial. Exemplo dos Territórios Rurais do Mato Grosso do Sul - Olivier François Vilpoux (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
Rural Territories program was created by the Ministry of Agrarian Development to promote local development from the interaction between local stakeholders. The functioning of this program depends on the cooperation between municipalities and the participation of local stakeholders in the Collegiate, entities responsible for definition and implementation of territorial policies. Based on this finding, research objective was to assess the relationship between members of Collegiate and the cooperation between them in the Territories of Dourados and Da Reforma , in Mato Grosso do Sul State. Data comes from SGE (Strategic Management System), provided by MDA. In the territories surveyed, participation of stakeholders in the management of projects that benefit the community is limited to few people. Many members of the Collegiate don’t participate in meetings and when they participate, are concerned with the interests of their own municipalities. Results confirm the lack of concern with territorial integration, with the realization of projects focused on one community or municipality, which impairs the functioning of Territories.